Temperature Insensitive PA Bias Circuit With Digital Control Interface Using InGaP/GaAs HBT Technology - Chang, Wei-Ling; Meng, Chinchun; Wong, Shyh-Chyi; Chien, Hwey; Huang, Guo-Wei (My University, 2015)
This paper demonstrates a new temperature insensitive bias circuit using a Wilson current mirror for the InGaP/GaAs HBT power amplifier. The Wilson current mirror has a high impedance node for connecting an on/off digital interface and a stable voltage node for injection of feedback signals to achieve a temperature insensitive bias. The fabricated output stage of the power amplifier with the feedback through the Wilson current source shows a stable bias current with current variation from 186 mA to 182 mA for the temperature range from 25 degrees C to 200 degrees C. A bias circuit without the feedback through the Wilson current source is also fabricated for comparison and shows a strong bias current variation over temperature.
Keywords: InGaP/GaAs HBT; temperature insensitive; power amplifier; Wilson current mirror